“Do we perceive the same reality?” Truth telling and persuasion techniques in Red Pilling narratives about the COVID-19 vaccine - K. Grailey; R. Gerrard; M. Kihanga; A. Buttenheim (SSM: Qualitative Research in Health)
Despite widespread public health campaigns, lower than desired COVID-19 vaccine uptake was seen across the USA. Vaccine hesitancy can be driven by the proliferation of misinformation online, shaping beliefs and vaccine acceptance. This study explored motivated reasoning and its role in the development of such beliefs, specifically using narratives about “red pilling” – a popular concept originating from the 1999 film ‘”The Matrix”.Comments responding to an online blog post by Steve Kirsch, requesting red pilling stories from his followers were analysed in a stepwise process, creating a codebook based on existing typologies for logical fallacies and persuasion techniques. Coded content were thematically analysed using a framework approach.The 1472 comments posted by June 22nd, 2022 were analysed. Fifty-three initial codes were created, condensed into a thematic framework with three overarching domains – “How did you get red pilled”, “Have you been able to red pill others” and “Living red pilled”. These domains contained 11 themes and 14 additional sub-themes. Commenters shared insights into becoming red-pilled, the significance of persuasive sources and how they went on to “red-pill” others. Data also illustrated an isolated life once “red-pilled”, whilst simultaneously being a member of a global network.Our analysis provides a rich insight into the strategies and scenarios that inspire red-pilling narratives and their consequences, particularly for public health initiatives such as vaccination programmes. Understanding the ideology that underpins the initiation and spread of misinformation can be utilised to pre-empt and minimise it, building trust across a broad range of world views.